New-Onset OCD and Juvenile Enthesitis-Related Arthritis after COVID-19 (Three Cases) - Saini, Tanya; Ma, Meiqian; Sandberg, Jesse; Farhadian, Bahare; Manko, Cindy; Xie, Yuhuan; Madan, Juliette; Bauer, Karen; Tran, Paula; Frankovich, Jennifer (Developmental neuroscience, 2025)
Abstract Introduction: Obsessive-compulsive disorder (OCD) is a mental health disorder characterized by obsessions and compulsions. There is a mounting body of evidence suggesting a link between OCD and inflammation. Neuropsychiatric deteriorations have been reported to follow COVID-19 infections, including OCD. Additionally, symptomatic arthritis has also been reported following COVID-19 infection. We aim to describe post-COVID-19 clinical deteriorations presenting to our multidisciplinary immune behavioral health clinic. Methods: One hundred and fifty-one prescreened patients were evaluated in our clinic between March 1, 2020 and August 1, 2024. We systematically searched charts for infection with SARS-CoV-2 and found 3 cases of confirmed COVID-19 infection that preceded an abrupt neuropsychiatric deterioration (in the absence of other detected infections). Per our clinic’s latest protocol, all patients underwent a full rheumatology and arthritis evaluation (regardless of joint complaints) including ultrasound imaging, which were used to objectively assess for effusions, synovitis, and capsulitis. Results: Two of the three patients met criteria for a PANS diagnosis. All 3 patients had new-onset OCD or reescalation of OCD with new obsessions/compulsions/rituals post-COVID-19 and all three had imaging findings of effusions +/− synovitis +/− capsulitis despite not having significant complaints of joint pain. Joint pain complaints evolved after psychiatric symptoms improved (because the capacity of the patient to articulate joint pain improved when they were less overwhelmed by intrusive thoughts). Immunomodulatory treatment began with nonsteroidal anti-inflammatory drugs (NSAIDs) and was escalated to disease-modifying antirheumatic drugs (DMARDs) in the 2 patients with synovitis +/− capsulitis. All 3 patients eventually returned to baseline neuropsychiatric health (minimal-to-no OCD and resolution of intense anxiety and mood instability) and also had improvement in arthritic findings after introduction of NSAID +/− DMARDs. Conclusion: Infections may result in systemic immune activation leading to inflammation. Thus, when patients have an acute neuropsychiatric deterioration (hypothesized to have been triggered by an infection), the situation may warrant evaluation for inflammation in other more accessible sites (e.g., joints). Use of this evidence of inflammation (as a sign of immune activation) is helpful since it is difficult to assess for brain inflammation, as clinical brain imaging has poor sensitivity for inflammation and biopsy of the striatum (and other areas involved in OCD) is difficult and limited by risk. In our cases, early joint imaging not only helped confirm signs of systemic inflammation in the setting of neuropsychiatric symptoms, but it also allowed for earlier initiation of immunomodulatory treatment.